Liquid-Liquid Equilibrium of the System {Peanut Biodiesel + Glycerol + Ethanol} at Atmospheric Pressure - Toledo, Iza Estevam Pedrosa; Ferreira-Pinto, Leandro [UNESP]; Voll, Fernando Augusto Pedersen; Cardozo-Filho, Lucio; Meili, Lucas; Coêlho, Dayana De Gusmão; Carvalho, Sandra Helena Vieira De; Soletti, João Inácio (American Chemical Society (ACS), 2019)
This study reports experimental data for the liquid-liquid equilibrium (LLE) for a {peanut biodiesel (1) + glycerol (2) + ethanol (3)} system at 303.15 K and 323.15 K at atmospheric pressure. Solubility (binodal) curves were obtained by a cloud-point method. The reliability of the experimental data was confirmed using the Hand and Othmer-Tobias correlations. The regression coefficients were above 0.97 for all data sets. The universal quasichemical model was successfully used to correlate LLE data, which showed root-mean-square deviations of 0.99%, indicating accuracy close to experimental uncertainties.